2021
DOI: 10.5194/hess-2021-127
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking Data-Driven Rainfall-Runoff Models in Great Britain: A comparison of LSTM-based models with four lumped conceptual models

Abstract: Abstract. Long short-term memory models (LSTMs) are recurrent neural networks from the emerging field of Deep Learning (DL), which have shown recent promise when predicting time-series especially when data are abundant. Rainfall-runoff modelling presents a challenge, yet accurate hydrological models are vital for flood forecasting, hazard impact assessment, and to assess the potential effects of climate change on floods and water resources. In this study, we compare the performance of two DL-based models, a LS… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
40
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 0 publications
4
40
3
Order By: Relevance
“…catchment attributes) features outperformed the regional LSTM model that did not take into account any static features as well as all tested local benchmark models. In the climatic context of Great Britain and on a sample of 518 catchments, Lees et al (2021) observed also an outperformance of regional LSTM models over four conceptual benchmark models, namely SACRAMENTO, ARNOVIC, TOPMODEL and PRMS. These studies (Kratzert et al, 2018(Kratzert et al, , 2019aLees et al, 2021) show that regional training of the LSTM brings performance improvement when compared with local training since regional models learn better.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…catchment attributes) features outperformed the regional LSTM model that did not take into account any static features as well as all tested local benchmark models. In the climatic context of Great Britain and on a sample of 518 catchments, Lees et al (2021) observed also an outperformance of regional LSTM models over four conceptual benchmark models, namely SACRAMENTO, ARNOVIC, TOPMODEL and PRMS. These studies (Kratzert et al, 2018(Kratzert et al, , 2019aLees et al, 2021) show that regional training of the LSTM brings performance improvement when compared with local training since regional models learn better.…”
mentioning
confidence: 85%
“…In the climatic context of Great Britain and on a sample of 518 catchments, Lees et al (2021) observed also an outperformance of regional LSTM models over four conceptual benchmark models, namely SACRAMENTO, ARNOVIC, TOPMODEL and PRMS. These studies (Kratzert et al, 2018(Kratzert et al, , 2019aLees et al, 2021) show that regional training of the LSTM brings performance improvement when compared with local training since regional models learn better. It is therefore tried to improve learning by increasing the number of train catchments.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The Nash-Sutcliffe Efficiency (NSE) (Nash and Sutcliffe, 1970), Equation 13is perhaps the most widely used performance measure in hydrology (Ewen, 2011). It has been used for many years and there is extensive literature discussing its strengths and weaknesses (Gupta et al, 2009). Owing to the squared term in the definition of NSE, it is more heavily influenced by high flows.…”
Section: Evaluation Protocolmentioning
confidence: 99%
“…and a variability (SDError Equation 16) term (Gupta et al, 2009). The bias term measures the error in predicting the mean flow.…”
Section: Evaluation Protocolmentioning
confidence: 99%